ClearCell® FX, a label‐free microfluidics technology for enrichment of viable circulating tumor cells. Issue 12 (6th August 2018) - Lee, Yifang; Guan, Guofeng; Bhagat, Ali Asgar
Abstract: Circulating tumor cells (CTCs) dissociate from primary tumor into the bloodstream, and carry with them cancer's fingerprints as well as the potential to turn aggressive and metastasize. In order to understand CTCs and develop clinical utility, different methods of enrichment and isolation of CTCs can be used. Here, we report the use of a label‐free platform, ClearCell® FX which isolates CTCs by their mechanical features and its advantages. The technology utilizes Dean Flow Fractionation (DFF) principle in a spiral microfluidics system to separate the larger CTCs from smaller blood cells. The gentle and fast workflow allows for a range of downstream assays to be performed on the intact CTCs, particularly studies that examine an epithelial cell adhesion molecular (EpCAM)‐independent population. Viable, intact cells are also retrievable for development of culture or in vivo models. © 2018 International Society for Advancement of Cytometry